Impact of moisturizing pretreatments on small reusable dental instruments cleanliness and mechanics - Xiuyu Tang; Yi Min; Yixuan Geng; Huan Huang; Tianjuan Xia (PLoS ONE, 2026)
Background Effective cleaning of reusable dental instruments is crucial. Pre-cleaning moisturizing aims to prevent bioburden from drying; however, its comparative efficacy and impact on instrument integrity require further investigation. Aim This in vitro study evaluated the effects of various moisturizing pretreatments on the cleaning efficacy and mechanical properties of small reusable dental instruments. Methods Surgical burs (fissure, round) and Nickel-Titanium (NiTi) files (n = 30/type) underwent four cycles of use and reprocessing with one of three pretreatments: water (control), a multi-enzyme cleaner, or a professional moisturizer (instrument transport gel). Cleanliness was assessed by microscopy (25 × magnification) and Adenosine Triphosphate (ATP) testing. Scanning Electron Microscope (SEM) and Energy Dispersive X-ray Spectroscopy (EDS) were used to evaluate surface contamination and wear after cycling. Results The professional moisturizer yielded significantly higher cleanliness scores and lower ATP values across all instrument types compared to the water or multi-enzyme cleaner groups (P < 0.05), maintaining consistent cleaning efficacy. SEM revealed less surface contaminant residue in the professional moisturizer group. However, SEM also indicated more frequent structural alterations on burs (fissure and round) pretreated with the professional moisturizer. EDS analysis suggested better preservation of the instruments’ native elemental composition in the professional moisturizer group. Conclusions Professional moisturizer pretreatment significantly improved cleaning and reduced bioburden on reusable dental instruments. Although superior in cleaning, the observed structural alterations on burs pretreated with the professional moisturizer warrant further investigation into its long-term effects on specific instrument material integrity before broad recommendations can be made for extending instrument lifespan.